K-Means Clustering Segmentation Based on Consumer Interest Using SPSS Program at XYZ Indonesia Customers - Utomo, Pontjo; Tampi, Mia; Claudia, Diny; Haikal, Jerry (Dinasti International Journal of Digital Business Management, 2025)
This study aims to understand the preferences and behavior of PT XYZ Indonesia's customers through K-Means Clustering segmentation analysis using the SPSS program. PT XYZ Indonesia, a restaurant that combines Japanese and Indonesian cuisine, has adopted various digital marketing strategies to enhance their online brand presence and strengthen customer relationships. In this study, data was collected through questionnaires filled out by 102 respondents who are customers of PT XYZ Indonesia. The data includes demographic variables such as gender, age, marital status, occupation, monthly income, as well as consumer behavior variables such as ordering platforms, information sources, visit frequency, restaurant location distance, and menu preferences. Through K-Means Clustering analysis, customers were grouped into six different clusters based on their interests and behavior. One prominent cluster is Cluster 3, which consists of young customers who are active on social media and frequently order food through online platforms such as Shopee Food. This cluster has key characteristics such as being male, 27 years old, single, working as private employees with a monthly income between 5 to 10 million rupiah, and having a specific preference for the Enog Berger Mayo menu. This study provides significant business implications for PT XYZ Indonesia, including increasing promotional activities on social media, offering exclusive discounts through online platforms, optimizing restaurant locations, developing menus that are favored by customers, and improving delivery services. By implementing the right strategies based on these segmentation results, PT XYZ Indonesia can enhance customer satisfaction, strengthen loyalty, and improve their market position. This study also emphasizes the importance of using segmentation techniques to understand consumer preferences and behavior in directing more effective and efficient marketing strategies.